Synthesis, Crystal Structure and Antioxidation Study of Cadmium(II) Complex with bis(N-Methylbenzimidazol-2-ylmethyl)aniline - Zhang, Yanhui; Shi, Furong; Bai, Yuchen; Wang, Xiaoli; Chen, Chengyong; Zhang, Jiawen; Wu, Huilu (Asian Journal of Chemistry, 2014)
A complex of cadmium(II) picrate (pic) with bis(N-methylbenzimidazol-2-ylmethyl)aniline (Mebba), with composition [Cd(Mebba)2](pic)2, was synthesized and characterized by elemental analysis, electrical conductivity, IR and UV/visible spectral measurements. The crystal structure of the cadmium(II) complex has been determined by single-crystal X-ray diffraction. The Cd(II) cation is bonded to two Mebba ligands through four benzimidazole nitrogen atoms and two aniline nitrogen atoms, resulting in a distorted octahedral geometry. The ligand Mebba and Cd(II) complexes have scavenging effects for hydroxyl radicals and complex shows stronger scavenging effects for hydroxyl radicals.